Chemistry in context : (Mc Graw Hill Higher Education, 2006)
Following in the tradition of the first four editions, the goal of this market leading textbook, Chemistry in Context, fifth edition, is to establish chemical principles on a need-to-know basis within a contextual framework of significant social, political, economic and ethical issues. The non traditional approach of Chemistry in Context reflect today's technological issues and the chemistry principles imbedded within them. Global warming, alternate fuels, nutrition, and genetic engineering are examples of issues that are covered in CIC.